2009
DOI: 10.1179/136217109x427485
|View full text |Cite
|
Sign up to set email alerts
|

Welding distortion investigation in fillet welded joint and structure based on iterative substructure method

Abstract: In this paper, prediction and controlling angular distortion in fillet welded joint and structure were investigated. First, two methods to reduce angular distortion in fillet welded joint were investigated by experimental and numerical analysis. One was to apply a constant external force in-process and the other was rigid clamping. In numerical analysis, a new in-house finite element code has been developed based on the idea of iterative substructure method (ISM) to calculate welding distortion in rational tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Additionally, in Fig. 7b, which is the x direction displacement distribution during welding, it is confirmed that a distribution of negative displacement is seen at the start point of the weld [1] (the bracketed numbers are shown in the figure), and a distribution of positive displacement is seen at the end point of the weld [2]. These distributions are caused by thermal expansion in the vicinity of the weld.…”
Section: Full Field Time Series Measurement Of 3d Deformation During ...supporting
confidence: 60%
See 1 more Smart Citation
“…Additionally, in Fig. 7b, which is the x direction displacement distribution during welding, it is confirmed that a distribution of negative displacement is seen at the start point of the weld [1] (the bracketed numbers are shown in the figure), and a distribution of positive displacement is seen at the end point of the weld [2]. These distributions are caused by thermal expansion in the vicinity of the weld.…”
Section: Full Field Time Series Measurement Of 3d Deformation During ...supporting
confidence: 60%
“…Displacement during welding provides important information to understand the mechanisms of welding deformation and residual stress. In particular, if welding deformation can be measured sequentially and the displacement distribution over full field can be measured, such as the results obtained by finite element analysis or other numerical analysis, 1,2 they can be valuable information.…”
Section: Introductionmentioning
confidence: 99%
“…This measure is also of great importance for the welding process [16]. For example, Kim proved that external force imposed normal to the plate during the cooling stage was effective to reduce the angular distortion during welding [17] and a similar conclusion was reached by Wang et al [18].…”
Section: Introductionmentioning
confidence: 64%
“…8 Meanwhile, advanced modelling and simulation techniques have been variously developed: material modelling that considers microstructural effects, 9, 10 double-ellipsoidal moving-heat-source modelling, 11, 12 and the fast computation using the iterative substructure method. 13, 14 Arc-physics-based heat-source modelling has recently enabled the predictive simulation of weld angular distortion based on welding conditions. 15 Thus, computational welding mechanics has great potential for accurately predicting and clarifying the weld shrinkage and distortion.…”
Section: Introductionmentioning
confidence: 99%